Jotvingių kalbos rekonstrukcijos klausimai - Hasiuk, Michał (Baltistica, 1989)
THE PROBLEM OF RECONSTRUCTING THE YATVINGIAN LANGUAGE The occurrence of the diphthong [ei] and of the consonants [s] and [z] is assumed as characteristic of the Yatvingian language. The same two features are also peculiar to Old Prussian. In the Lithuanian language we find [ie], [š], and [ž] as the respective counterparts. What we propose for the characterization of Yatvingian is to take into consideration the possibility of the depalatalization process which the following phenomena found in the Lithuanian dialect of Seinai (Polish Sejny) testify to: (1) the occurrence of the consonants [š, ž, r] without their palatal counterparts; (2) partial depalatalization of [s, z, l] only before front vowels; (3) partial depalatalization of labial consonants [p, b, m, v]. The depalatalization of the consonants enumerated under (1), (2) and (3) is connected with the centralization and lowering of the following front vowels [i:], [i], [ie], [e:], [x], [x:]. The phenomenon of depalatalization is also known today in some other Lithuanian dialects. Some spellings found in Old Prussian texts point to depalatalization having occurred in this language. In the Polish-Yatvingian vocabulary, discovered in 1983, there is also evidence of depalatalization of labial consonants.